AODWE-008 Multicentre ecco collaborative group study to evaluate the need for re-intervention following multimodal treatment in crohn`s disease with perianal fistula. (17th June 2017) - Black, C; Pugliese, D; Sahnan, K; Hart, A; Fiorino, G; Armuzzi, A; Katsanos, K; Christodoulou, D; Selinger, C; Maconi, G; Kopylov, U; Bosca-Watts, M; et al.
Abstract : Introduction: Treatment paradigms for Crohn's disease with perianal fistula (CD-PAF) are still evolving and so far, considered to have disappointing rates of complete healing. We aimed to study the impact of multidisciplinary multimodality treatment approach in CD-PAF on the recurrence rates of fistula and need for re-interventions. Method: This was a multinational multicentre retrospective cohort study with data collected in CD patients who developed fistula from 2010 to 2015. Multidisciplinary multimodality approach was defined as using a combination of medical treatments (antibiotics, immunomodulators, and biologics) along with surgical approach (examination under anaesthesia (EUA) +/- Seton drainage) at diagnosis. Results: 253 adult onset CD-PAF patients were included. There was significant difference in fistula healing rates between simple and complex fistulae (complete healing 60% vs 41%, p=0.015). 52% of patients who received multimodality treatment had complete fistula healing. 27% of simple fistula and 40.3% of the complex patients had recurrent fistula needing re-intervention at a median of 12 months (range 1–36 months) from diagnosis of fistula. 22% of those with complete healing needed repeat surgery compared to 49% with partial healing and 71% in those with no healing (p=<0.001). Only 26% of the 141 patients having multidisciplinary multimodal treatment needed surgical re-intervention when compared to 59% without this( P=<0.001).Univariate analysis showed complex (p=0.008), absence of multidisciplinary approach (p=<0.001), EUA (p=0.005), combined immunosuppression (p=0.032), presence of proctitis (p=<0.001) as factors impacting need for re-intervention but there was no impact of age, gender, smoking status, mode of presentation, Montreal class, presence of anal stenosis and thiopurine use alone. On logistic regression, absence of multi-disciplinary approach (OR 2.8, 95% CI: 1.4–5.6) and presence of proctitis OR 2.2, 95% CI: 1.2, 3.9) were predictors for re-intervention. Conclusion: In this multicentre cohort study, complete fistula healing rates were higher and the recurrence rates lower than previously reported. Presence of proctitis and lack of multidisciplinary approach are predictors for recurrence and re-intervention for CD-PAF. Disclosure of Interest: None Declared